Left Parietal Craniotomy for Resection of Grade IV Arteriovenous Malformation: 2-Dimensional Operative Video. Issue 4 (24th January 2020) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Parieto-occipital arteriovenous malformations (AVMs) are the second most common site for cranial AVMs. These lesions are defined as eloquent when the nidus involves either the postcentral gyrus or the occipital pole. If located on the dominant hemisphere, these lesions can also involve the arcuate fasciculus ventrally. This patient had a large unruptured Spetzler-Martin grade IV AVM within the parieto-occipital region extending deeply to the ventricle, following presentation with a seizure. The digital subtraction angiography demonstrated feeding vessels from both the middle cerebral artery and posterior cerebral artery distributions. Despite the high Spetzler-Martin grade, the lesion demonstrated favorable features such as a compact nidus, convexity presence, and lack of involvement of the precentral and postcentral gyrus. Preoperative embolization was utilized. The AVM was successfully resected both superficially and deeply to the level of the atrium of the lateral ventricle. Postoperative angiography demonstrated complete removal of the AVM, and the patient made a complete recovery from the procedure. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona.